New mathematics teachers’ learning when participating in induction on mathematics education – a case study of two lower secondary teachers - Krog Skott, Charlotte; Laursen Falkenberg, Louise; Redder Honoré, Ida (NOMAD Nordic Studies in Mathematics Education, 2021)
Newly qualified mathematics teachers often face teaching problems during their initial teaching years. We report on a study in which we designed an induction programme in mathematics education to support new teachers in tackling these problems. Using a social practice perspective, we investigate what and how two new lower secondary teachers learn by participating in the programme. We show that, while one teacher exceeds our expectations for learning, the other learns very little. We also show that the two teachers’ learning is reflexively related to school-local and broader contexts, which helps to explain the differences in their learning.